2004
DOI: 10.1128/mcb.24.11.5005-5015.2004
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the ped/pea-15 Gene Causes Diabetes by Impairing Glucose-Stimulated Insulin Secretion in Addition to Insulin Action

Abstract: Overexpression of the ped/pea-15 gene is a common feature of type 2 diabetes. In the present work, we show that transgenic mice ubiquitously overexpressing ped/pea-15 exhibited mildly elevated random-fed blood glucose levels and decreased glucose tolerance. Treatment with a 60% fat diet led ped/pea-15 transgenic mice to develop diabetes. Consistent with insulin resistance in these mice, insulin administration reduced glucose levels by only 35% after 45 min, compared to 70% in control mice. In vivo, insulin-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
118
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(125 citation statements)
references
References 37 publications
7
118
0
Order By: Relevance
“…Linear regression analysis performed as described in the Subjects and methods section revealed a correlation between PEA15 levels in PBLs and glucose disposal (r=−0.557, p=0.01) in cells from type 2 diabetic subjects [4], this overexpression occurs at both the mRNA and protein level indicating that, as previously demonstrated in cells from type 2 diabetic subjects [4], it is caused, at least in part, by a transcriptional abnormality. Earlier studies in isolated cells and in vivo showed that PEA15 binds to and increases the cellular stability of PLD1, deregulating PKC signalling and impairing insulin-dependent glucose disposal [17,18]. We now show that enhanced PLD1 stability also appears to occur in PBLs from type 2 diabetic subjects and FDR, suggesting that it occurs in individuals who overexpress PEA15.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Linear regression analysis performed as described in the Subjects and methods section revealed a correlation between PEA15 levels in PBLs and glucose disposal (r=−0.557, p=0.01) in cells from type 2 diabetic subjects [4], this overexpression occurs at both the mRNA and protein level indicating that, as previously demonstrated in cells from type 2 diabetic subjects [4], it is caused, at least in part, by a transcriptional abnormality. Earlier studies in isolated cells and in vivo showed that PEA15 binds to and increases the cellular stability of PLD1, deregulating PKC signalling and impairing insulin-dependent glucose disposal [17,18]. We now show that enhanced PLD1 stability also appears to occur in PBLs from type 2 diabetic subjects and FDR, suggesting that it occurs in individuals who overexpress PEA15.…”
Section: Discussionsupporting
confidence: 55%
“…In transgenic mice fed high-fat diets, the overexpression of Pea15 leads to diabetes [18]. In humans, no genetic variability accounting for the differential expression of the PEA15 gene has been identified to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PEA-15/PED plays an important role in glucose metabolism and its overexpression contributes to the development of diabetes mellitus (Vigliotta et al, 2004). However, the question whether PEA-15 plays a role in glucose metabolism in cancer cells has not been addressed so far.…”
mentioning
confidence: 99%